Pengaruh Waktu Penggantian Ransum BR1 dengan BR2 terhadap Performa Broiler - Sari Suryanah; Nilawati Widjaja; Tedi Akhdiat; Hilman Permana; Indra Setiawan (University of Insan Cendekia Mandiri, 2023)
This research aimed to find out how the effect of replacing BR1 with BR2 on broiler performance. The research method was experimental using a Completely Randomized Design (CRD) with 5 treatments consisted of R1: giving BR1 aged 1 to 35 days, R2: giving BR2 aged 1 to 35 days, R3: giving BR1 aged 1 to 7 days and giving BR2 aged 8 to 35 days, R4: giving BR1 aged 1 to 14 days and giving BR2 aged 15 to 35 days, R5: giving BR1 aged 1 to 21 days and giving BR2 aged 22 to 35 days. Each treatment was replicated 5 times. The observed variables were daily ration consumption, daily body weight gain, ration conversion. Data were analyzed by variance analysis, if there was an effect of treatment, it was continued with Duncan's Multiple Range Test. The conclusion of this research was that the replacement of BR1 to BR2 rations had a significant effect on daily ration consumption and ration conversion, but had no significant effect on daily body weight gain of broilers. Giving BR1 for 35 days resulted in the lowest daily ration consumption, daily body weight gain and ration conversion.